BİLATERAL ANTERİOR OPERKÜLER SENDROM (FOIX-CHAVANY-MARIE SENDROMU): BİR OLGU BİLDİRİMİ - ERTAN, Sibel; FALİHİ, Afrodit; GÖKSAN, Baki; KIZILTAN, Güneş (Cerrahpaşa Medical Journal, 2014)
Background.- Facio-pharyngo-glosso-masticatory voluntary diplegia with retained automatic movements is called Foix-Chavany-Marie syndrome. This rare syndrome is caused by bilateral lesions of the frontal operculum or their corticofugal projections. Observation.- We present a case of acute anarthria and facio-pharyngo-glosso-masticatory diplegia with automatic voluntary dissociation, i.e. bilateral anterior opercular syndrome (Foix-Chavany-Marie syndrome) as the result of two successive, right and left, strokes that caused bilateral frontal operculum damage. Though completely speechless, the patient was neither aphasic and nor apraxic. Several etiologies and the clinical and radiological features of this rare syndrome were discussed. The differential diagnosis of the syndrome from subcortical suprabulbar paralysis, peripheral lesions of the cranial nerves and vertebrobasilar ischemic strokes of the brainstem was made.